Rare ILD/DPLD 2018
DOI: 10.1183/13993003.congress-2018.pa3035
|View full text |Cite
|
Sign up to set email alerts
|

The presence of staphylococcal superantigens in nasal swabs and correlation with activity of granulomatosis with polyangiitis (GPA) in own material.

Abstract: The work was created within the statutory activity of the National Research Institute of Tuberulosis and Lung Diseases in Warsaw, Poland, research task nr 1.10 "Molecular epidemiological investigation among staphylococci isolated from patients with granulomatosis with polyangiitis".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Recently, multiple sources of evidence have reinforced the concept of the central pathogenetic role of NETs in the pathogenesis of AAV as a source for the formation of ANCA [39]. There were several clinical studies evaluating a critical role of SAgs for GPA activity [15,40,41], but none, so far, investigated, whether there is a relation between SAgs presence and ANCA levels in patients with GPA. Our study seems to be the first analyzing this association.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, multiple sources of evidence have reinforced the concept of the central pathogenetic role of NETs in the pathogenesis of AAV as a source for the formation of ANCA [39]. There were several clinical studies evaluating a critical role of SAgs for GPA activity [15,40,41], but none, so far, investigated, whether there is a relation between SAgs presence and ANCA levels in patients with GPA. Our study seems to be the first analyzing this association.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study [15], we analyzed the relationship between the presence of SAgs in nasal swabs and GPA activity, but the aim of the current study was to determine the relationship between ANCA concentration and disease activity, while taking into account the association between ANCA formation and the presence of SAgs in nasal swabs in patients with GPA.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been shown that a treatment with cotrimoxazole could prevent the occurrence of relapse [35]. The main influence of S. aureus on AAV activity is mainly attributed to its superantigens (SAgs), an extremely potent immunostimulatory molecules [36,37], but so far, the results of clinical studies evaluating a critical role of SAgs for AAV activity have not been unequivocal [38,39].…”
Section: The Mechanism Of Anca Formation In Aavmentioning
confidence: 99%
“…Conversely, Fijolek and colleagues identified the presence of at least one SAg in 34.8% of GPA patients, but its presence was not associated with disease activity. However, earlier studies had not revealed a correlation between the presence of SAg genes and the expansion of specific T cell subsets in peripheral blood [116].…”
Section: Staphylococcus Aureus and Granulomatosis With Polyangiitismentioning
confidence: 99%